Optimization Of E-Litigation-Based Trial Implementation As A Strategy To Prevent Bribery And Gratification (Comparatory Study Of E-Litigation Implementation In Malaysia And Singapore) - Yoesuf, Juliani Paramitha; Mulyono; Siti Nur Intihani; Efridani Lubis; Muhammad Fahruddin; Sinta Elviyanti (Universitas Djuanda, 2024)
The E-Court system in Indonesia is an embodiment of the principles of simple, fast and low-cost justice, as well as technological transformation in the case administration system in court. The E-Court system has been running in all courts in Indonesia since 2018, then in 2019 the Supreme Court implemented the E-Litigation system, namely electronic-based trials and the arrangements continue to be refined, especially with the issuance of Supreme Court Regulation Number 7 of 2022 concerning Amendments to Supreme Court Regulation Number 1 2019 concerning Electronic Administration of Cases and Trials in Court. By implementing E-Litigation, apart from making trials easier and saving time, it will of course also reduce the intensity of meetings with the parties so that bribery and gratification do not occur in the judicial environment. Seeing that the implementation of the electronic trial system in Indonesia is still relatively new, it is necessary to compare with other countries such as Malaysia (2011) and Singapore (2015) which first implemented both E-Court and E-Litigation to see what things need to be optimized in implementation of an electronic trial system so that it can prevent the practice of bribery and gratification. The research methodology used in this research is normative-empirical legal research. The problems to be studied are: 1) What is the trial mechanism through the E-litigation system in Indonesia, Malaysia and Singapore? 2) How to optimize the implementation of e-litigation based trials in reducing bribery and gratification?